(untitled) (Research, Society and Development, 2021)
His study was carried out in the Amazon agroecosystems of communities in the Alto Rio Solimões, southwest of the State of Amazonas. The objective was to present the action of the forms of use and management of soils developed by family farmers in terms of fertility in established components such as: backyards, farmlands, capoeiras (fallow) and forests of existing agroecosystems. Two communities of family farmers in the municipality of Benjamin Constant were randomly chosen, one in a lowland area, called São José, and another in terra firme, called Nova Aliança. The statistical analysis used had a randomized block design with four replications each, where the plots were related to the components of the agroecosystems (backyard, farmland, capoeira and forest) and the depths were related as sub-plots. Due to the influence of the organic matter content on the surface, the results obtained show us that depending on the vegetation cover and the type of soil, the concentration of nutrients is greater in the smaller depths, being essential for the conservation of these soils. The results also demonstrate that the forms of management adopted by family farmers, modifying landscapes based on their daily life and work, have an effect on soil fertility.